Implementasi Potensi Kecerdasan Siswa SMP dengan Konsep Multiple Intelligence - Syairul Bahar (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2022)
The purpose of this research produces the accuracy of potential intelligence possessed by students and implement it in the learning process. This research uses a descriptive method with a qualitative approach. The data collection techniques use observation and questionnaires. The object of this research is the students of Bunda Junior High School (SMP). The population in this research are students of SMP Bunda with a total population of 33 to be studied. Judging from the small amount population, the researcher uses Saturation Sampling. Based on Howard Gardner's concept of multiple intelligence, there are nine intelligences in humans, are Linguistic Intelligence, Logical-Mathematical Intelligence, Spatial Intelligence, Musical Intelligence, Naturalist Intelligence, Physical-Kinesthetic Intelligence, Intelligence Interpersonal, Intrapersonal Intelligence, and Existential Intelligence. Based on the results of the research, most students of SMP Bunda are dominated by intrapersonal intelligence as much as 36% and musical intelligence as much as 24%. The implementation in the learning process, are 1) the teacher must empower all types of intelligence in teaching learning process with the aim that all students can find their respective intelligence, 2) the teachers also must optimize the dominant intelligence of each student in the teaching learning process. So, teachers play an active role in developing the potential of students. Teachers must recognize the potential intelligence of their students in order to get success in the future.